Escalation to Barbiturate-Induced Coma for Refractory Seizures after Liver Transplantation. (10th January 2022) - Miles, Brittany; Mujtaba, Muhammad; Merwat, Shehzad; Kulkarni, Rupak; Fair, Jeffrey; Kueht, Michael
Abstract : Seizures after liver transplantation were previously thought to be a reliable harbinger of catastrophe, but more recent studies have found seizure activity to be relatively common, and most cases do not result in a poor outcome. Generalized seizures are the most common, and they typically occur de novo within the first two weeks after transplantation. The underlying cause for seizure activity in these patients may be complex, with potential etiologies including metabolic, infectious, cerebrovascular, and medication-induced causes. Identification of the underlying cause and the use of antiepileptic drugs (AEDs) is crucial for minimizing risk to the patient's neurologic and overall health. In this report, we present the case of a patient with refractory seizures unresponsive to conventional treatment, requiring prolonged barbiturate burst suppression with ventilator support. Seizure activity eventually ceased, and the patient made a full recovery.